Well-defined atomic hydrogen target driven by electromagnetic shock wave for stopping power measurement. (21st September 2015) - Kondo, Kotaro; Yokozuka, Tomohiro; Oguri, Yoshiyuki
Abstract: The precise estimation of stopping power is crucial to predict the beam energy loss in the target for heavy-ion fusion and heavy-ion-driven high-energy density physics experiments. The electromagnetic shock wave has been proposed to generate a well-defined atomic hydrogen target for the stopping power measurement with dissociation effects. We measured the angular distribution profile of the discharge plasma and the plasma velocity in the electromagnetic shock tube by high-speed framing cameras. To improve the uniformity of the discharge plasma and the velocity, an external magnetic field was applied in the electromagnetic shock tube. The plasma velocity was up to approximately 40 km/s for an initial hydrogen gas pressure of 100 Pa and the velocity decreased with the initial pressure and the propagation length. The framing cameras showed that angular distributions of the discharge plasmas were not uniform and the initial angular distributions were important for the development of plasma profiles. The interaction of the plasma with the external magnetic field was estimated using the ratio of the plasma dynamic pressure to the magnetic pressure. The estimations offer more magnetic fields to improve the discharge uniformity due to the interaction.